The effectiveness of using music and song in the teaching of grammar at Sek. Keb. Pengkalan Nyireh Besut, Terengganu / Siti Zaleha Ariffin - Ariffin, Siti Zaleha (2001)
This research concentrates on the importance of music and song as teaching material in an English language classroom. It tries to confirm that the used of music and song as a strategy can enhance pupils interest in learning the English Language. The general aim of this study is to find out the implications of music and song towards English Language learning in the classroom. The study begins with the background of music and song, the different types of music and songs and different findings from previous researches. Since music and song is too wide, this research will concentrate on the use of a jazz chant and a song in enhancing pupils’ language learning. The focus will be on the teaching of grammar.